Pengaruh Skema Kompensasi Dan Gender Terhadap Penilaian Etis Manager Atas Investasi Berlebih Pada CSR - Zuwitha Marshela Sri Wahyuni; Sany Dwita; Halmawati Halmawati (Jurnal Eksplorasi Akuntansi, 2019)
This study aims to test the influence of pay scheme and gender on managers’ ethical judgements in regards to overinvestment in corporate social responsibility. Drawing from atribution theory, this study predicts that managers with different payscheme and different gender will accordingly make different ethical judgements on overinvestment in CSR. The data were collected by conducting a quasi-experimentation. The results of this study show evidence that managers with overinvestment hindering payscheme (a payscheme that gives managers no incentive to overinvestment in CSR) are more likely to consider overinvestment in CSR as more unethical than those with overinvestment inducing payscheme. The results also show that gender has no influence on manager’s ethical judgement on overinvestment in CSR. This study contributes to management accounting and accounting ethic literature by identifying how the role of payscheme and gender influence ethical judgement on overinvestment in CSR.